Trematodosis pada Sapi dan Kerbau di Wilayah Endemik Schistosomiasis di Provinsi Sulawesi Tengah, Indonesia - Novericko Ginger Budiono; Fadjar Satrija; Yusuf Ridwan; Defriska Nur; . Hasmawati (Jurnal Ilmu Pertanian Indonesia, 2018)
Cattle and buffaloes have economic value as a source of protein and draught power. The people of Sulawesi also use buffalo in various custom and religious activities. Infections by Trematodes may disrupt livestock productivity. In Indonesia, endemic Schistosomiasis can only be found in Central Sulawesi, Indonesia (Lindu, Napu, and Bada Valleys). There is no data on the status of Trematode infection in cattle and buffalo animals in the area. The study was conducted using a cross-sectional design to measure the prevalence of Trematodosis in cattle and buffalo around the endemic areas of Schistosomiasis in July-November 2016. A total of 261 stool samples consisting of 173 cattle and 88 buffaloes from 7 villages (Anca, Bewa, Mount Gintu, Sedoa, Wangga, Watumaeta, and Wuasa Villages) were collected and stored at 2-8 °C until further analysis. The Danish Bilharziasis Laboratory method was chosen to quantify the infection by trematodes. The prevalence of the overall trematodosis of this study was 85.06%. The prevalence of Trematodosis in buffalo was higher than in cattle and differed statistically (P<0.05). The highest prevalence was Paramphistomiasis (75.48%), followed by Fascioliasis (67.05%) and Schistosomiasis japonica (30.27%). The trematodosis prevalence of each village also varied and differed statistically (P<0.05). Intensites of infection of mild, moderate, and severe infections were reported in this study. Mixed infections by two even three species of trematodes were reported in this study. Two newly endemic Schistosomiasis villages are reported, namely Bewa Village and Gunung Gintu. The results of this study are used as a basis for controlling Trematodosis in large ruminants in endemic areas especially with zoonotic potential.